2008
DOI: 10.1007/s10654-008-9239-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-economic burden of obesity in Europe

Abstract: Although overweight and obesity have long been recognised as major risk factors for a number of chronic diseases, lifestyle developments have led to substantial increases in bodyweight worldwide. In addition to their negative effects on health and quality of life, obesity and associated comorbidities may have a considerable impact on healthcare expenditures. The aim of this systematic review was to summarise cost estimates and compare costs attributable to obesity across different European countries. A structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(117 citation statements)
references
References 18 publications
(31 reference statements)
2
100
0
15
Order By: Relevance
“…6 Because of the clear epidemiological association between overweight and several diseases, it is not surprising that health-care expenditures for obese/overweight persons are higher than for normal weight persons. 7 In the Netherlands and other western countries prescription drugs constitute a large part of the health-care expenditures. 8 Most of the diseases associated with overweight are chronic in nature, and thus require chronic medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Because of the clear epidemiological association between overweight and several diseases, it is not surprising that health-care expenditures for obese/overweight persons are higher than for normal weight persons. 7 In the Netherlands and other western countries prescription drugs constitute a large part of the health-care expenditures. 8 Most of the diseases associated with overweight are chronic in nature, and thus require chronic medication.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9,10,12 Also medication data were mostly obtained through self-report, 13,[15][16][17][18][19] although some studies used data of GP records 9,10 or records of drug reimbursements. 11,12,14 For this study, data of the Doetinchem Cohort Study are used with measured rather than self-reported data on BMI.…”
Section: Introductionmentioning
confidence: 99%
“…These behaviors have adverse consequences on human health by increasing the risk of cardiovascular diseases, high blood pressure, raised blood cholesterol, type 2 diabetes, cancer and metabolic syndrome [3,4]. With the spreading of the obesity epidemic in many industrialized countries, the economic sustainability of the public-health system is threatened as a result of increasing medical expenditures due to these diet-related diseases [23,24].…”
Section: A Consumer Perspective Of Health and Environmental Sustainabmentioning
confidence: 99%
“…With respect to gender, the sample is representative of the population of the Lombardy region, to which Milan belongs. The sample is also representative of the Lombardy population for the age category 26-40, while there is an over-representation of young individuals (18)(19)(20)(21)(22)(23)(24)(25) and an under-representation of older ones (>65). This could be due to the fact that Milan is a university city and there are many students who live in the city, but are not actually residents.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…Life-styles, mainly, sedentary and high intake of calories derived from products containing intense doses of energy-dense elements such as fats and sugar together with the greater amount of food intake are the major responsible for the obesity positive trends. Genetics are believed to only account for a marginal 1% of the cases [1,2].Health consequences of obesity have also been frequently studied, and the list of related conditions keeps growing (type 2 diabetes, hypertension, cardiovascular diseases, some cancers, gallbladder disease, osteoarthritis, disabilities, psychosocial problems, etc). These diseases are mostly chronic, their trends, again, are positive, and the final result is a lower life expectancy, estimated around 9 years less on average.…”
mentioning
confidence: 99%